2023
DOI: 10.3389/fimmu.2023.1120010
|View full text |Cite
|
Sign up to set email alerts
|

Third SARS-CoV-2 vaccination and breakthrough infections enhance humoral and cellular immunity against variants of concern

Abstract: IntroductionSARS-CoV-2 vaccination is the leading strategy to prevent severe courses after SARS-CoV-2 infection. In our study, we analyzed humoral and cellular immune responses in detail to three consecutive homologous or heterologous SARS-CoV-2 vaccinations and breakthrough infections.MethodsPeripheral blood samples of n=20 individuals were analyzed in the time course of three SARS-CoV-2 vaccinations and/or breakthrough infection. S1-, RBD-, S2- and N-specific IgG antibodies were quantified using Luminex-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Increases in S-specific T cell responses have also been previously noted by others following mild or moderate BTI. 33 , 64 , 65 , 66 , 67 , 68 However, this increase was not observed in more severe and critical cases of infection where instead a delayed S-specific T cell response was observed. 69 Here, the largest increases in SARS2-specific T cell responses were observed in individuals with no pre-existing memory of non-S antigens.…”
Section: Discussionmentioning
confidence: 88%
“…Increases in S-specific T cell responses have also been previously noted by others following mild or moderate BTI. 33 , 64 , 65 , 66 , 67 , 68 However, this increase was not observed in more severe and critical cases of infection where instead a delayed S-specific T cell response was observed. 69 Here, the largest increases in SARS2-specific T cell responses were observed in individuals with no pre-existing memory of non-S antigens.…”
Section: Discussionmentioning
confidence: 88%
“…Memory T cell responses in 11 of 12 participants after heterologous DNA vaccination followed by boosting with mRNA vaccine were increased in both CD4+ and CD8+ T cells 33 . A study of memory T cell phenotypes after first vaccination showed increased numbers of EM and TEMRA CD4+ or CD8+ T cells but these were lower after the second and the third vaccination 34 . Our study is the first observation in a Thai heterologous booster vaccination program which investigates changes in memory T cell subpopulations upon in vitro stimulation of PBMC with Omicron peptide, compared to unstimulated circulating cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a reduced in vitro antibody inhibition capacity of non-hospitalized patients especially against delta and beta variants of SARS-CoV-2 was found, which might explain breakthrough infection of patients with mild course of disease. The importance of repetitive vaccinations has been shown by Ruhl et al [ 22 ]. In the multivariate analysis, CD4 + T cell counts were positively correlated with post-acute FAS score.…”
Section: Discussionmentioning
confidence: 99%